AN EMPIRICAL STUDY ON RISK AND OPPORTUNITIES OF USE OF ARTIFICIAL INTELLIGENCE IN THE INDIAN INSURANCE SECTOR - Pallathadka, Harikumar; Kirana Pallathadka, Laxmi (International Journal of Psychosocial Rehabilitation, 2021)
Studies have been done to understand the use cases of AI or Artificial intelligence, in theinsurance sector. Specifically, they aim to explore the scope and market penetration ofArtificial Intelligence in the insurance sector to overcome ongoing issues for better consumersatisfaction. Based on the concept of Artificial Intelligence, the conceptual model has beendeveloped. This conceptual model mainly aims at measuring the relation between ArtificialIntelligence and its use case in the insurance sector. These studies conclude specific practicalinsights that are considered helpful for the insurance companies while responding to thedissatisfied consumers and the other operational issuesPreviously, the party to the insurance contract, the insurer and insured, used to havedifferent information. It is crucial for understanding the insurance economies as asymmetrycauses strategic behavior. The insurer tries to get maximum data so that the behavior of theinsured may be inferred.